Intravesical administration of green tea extract attenuates the inflammatory response of bacterial cystitis – a rat model. (20th February 2014) - Rosenberg, Shilo; Horowitz, Ray; Coppenhagen‐Glazer, Shunit; Pizov, Galina; Elia, Anna; Gofrit, Ofer N.; Ginsburg, Isaac; Pode, Dov
<x xml:space="preserve">Abstract</x> Objective To explore the effect of intravesical instillation of green tea extract (GTE) on a rat model of bacterial cystitis. Materials and Methods In vitro bactericidal properties of GTE were analysed by adding GTE to a suspension of uropathogenic E. coli (UPEC), streaking on MacConkey agar, and incubating overnight. In vivo effects of intravesical instillation of GTE on bacterial cystitis was analysed using a rat model of bacterial cystitis. In all, 42 female Sabra rats weighing 200–260 g were divided into five groups. Parameters measured were bladder weight (percentage of the total rat weight), dipstick urine analysis and histopathological changes in the bladder. Histological changes evaluated were degree of oedema, mixed inflammatory infiltration, urothelial epithelial invasion by neutrophils and reactive atypia. Results No in vitro bactericidal activity was detected for GTE. Intravesical instillation of GTE did not cause damage to the rat bladders. Intravesical instillation of GTE attenuated the inflammatory response to UPEC‐SR71‐induced bacterial cystitis in this rat model. Conclusions Intravesical instillation of GTE attenuated the inflammatory response to UPEC‐SR71‐induced bacterial cystitis and is a novel approach to the treatment of bacterial cystitis. High concentrations of intravesical GTE did not cause histologically evident damage to the rat bladder. The results of this study are preliminary and further studies will be needed to explore the feasibility of using this approach in humans.